PEMANFAATAN SERPIHAN KAYU, RUMPUT ALANG-ALANG (Imperata cylindrica (L.) BEAUV.) DAN DAUN ACACIA MANGIUM WILLD. SEBAGAI MULSA ORGANIK UNTUK PENGENDALIAN GULMA - Herman Herman; Siti Fatonah (DINAMIKA PERTANIAN, 2013)
The aim of this research was to examine the effect of Wood Shavings, Reed, and Acacia Magnum leaf mulches on density and composition shoots of weed, determine the most effective mulch to control weed, and determine composition of arranged weed. The research was conducted at experimental biological farm of FMIPA Biology Riau University from March to May 2012. The treatment consisted of land without mulch, land with mulch of wood shavings, reed, and acacia magnum leaf. Each treatment was repeated twice. Each organic matter was spread on the soil surface with thickness of 5 cm for each plot 1 cm2 of size. The observation was conducted once every 4 week, namely 4 weeks, 8 weeks, and 12 weeks after being given mulch. The results showed that the Acacia Magnum leaf was the most effective organic mulch to control weed with the obstacle percentage of 54.22%. The weed which was hampered its emergence by Acacia Magnum leaf was wide weed leaf. Application of Acacia Magnum leaf mulch was able to change weed composition with the smallest proportion was wide leaf weed and narrow leaf weed proportion increased